2019
DOI: 10.1080/15548627.2019.1586246
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 and ALKBH5 oppositely regulate m6A modification of TFEB mRNA, which dictates the fate of hypoxia/reoxygenation-treated cardiomyocytes

Abstract: N 6-methyladenosine (m 6 A) mRNA modifications play critical roles in various biological processes. However, no study addresses the role of m 6 A in macroautophagy/autophagy. Here, we show that m 6 A modifications are increased in H/R-treated cardiomyocytes and ischemia/reperfusion (I/R)-treated mice heart. We found that METTL3 (methyltransferase like 3) is the primary factor involved in aberrant m 6 A modification. Silencing METTL3 enhances autophagic flux and inhibits apoptosis in H/R-treated cardiomyocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
339
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(357 citation statements)
references
References 41 publications
16
339
2
Order By: Relevance
“…As described previously (Song et al, 2019), we cultured HEK293T cells to perform the dual-luciferase reporter assays.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%
“…As described previously (Song et al, 2019), we cultured HEK293T cells to perform the dual-luciferase reporter assays.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%
“…Suppressing adipogenesis by promoting cell cycle transition in mitotic clonal expansion [89] YTHDF2 Inhibiting autophagy and adipogenesis by decreasing protein expression of ATG5 and ATG7 and shortening the lifespan of their m 6 A-modified mRNAs [87] Suppressing adipogenesis by increasing m 6 A methylation of CCNA2 and CDK2 and reversing the methylation effect of FTO on CCNA2 and CDK2 [90,91] Inhibiting adipogenesis via the downregulation of CCND1 [92] NAFLD FTO Down-regulating mitochondrial content and up-regulating TG deposition [101] Promoting hepatic fat accumulation by increasing the expression of lipogenic genes, including FASN, SCD and MOGAT1, and intracellular TG level in HepG2 cells [101] Increasing oxidative stress and lipid deposition [99] YTHDF2 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] METTL3 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] Hypertension m 6 A-SNPs EncodIing β1-adrenoreceptor, a hypertension-susceptibility candidate gene [108,109] Altering BP-related gene expression, mRNA stability and homeostasis [110] Cardiovascular diseases FTO Decreasing fibrosis and enhancing angiogenesis in mouse models of myocardial infarction [111] METTL3 Driving cardiomyocyte hypertrophy by catalyzing methylation of m 6 A on certain subsets of mRNAs [112] Decreasing eccentric cardiomyocyte remodeling and dysfunction [112] Inhibiting cellular autophagic flux and promoting apoptosis in hypoxia/reoxygenation-treated cardiomyocytes [113] Osteoporosis METTL3 Inhibiting adipogenesis and adipogenic differentiation via JAK1/STAT5/C/EBPβ pathway in bone marrow stem cells [119] Inhibiting osteoporosis pathological phenotypes, consisting of decreased bone mass and increased marrow adiposity via PTH/PTH1R signaling axis [118] FTO Promoting the differentiation of adipocyte and osteoblast by upregulating GDF11-FTO-PPARγ signalling way [116] Enhancing the stability of mRNA of proteins which function to protect osteoblasts from genotoxic damage through Hspa1a-NF-κB signaling way [120] Immune-related MDs ALKBH5 Expressing highly in organs enriched in immune cells with frequent immune reactions [10,123] METTL3 Stimulating T cell activation and the development of T lymphocytes in the thymus by regulating the translation of CD40, CD80 and TLR4 signaling adaptor TIRAP transcripts in den...…”
Section: Mettl14mentioning
confidence: 99%
“…Whereas, diminished METTL3 promotes eccentric cardiomyocyte remodeling and dysfunction [112]. Moreover, METTL3 upregulation inhibits cellular autophagic flux and promotes apoptosis in hypoxia/reoxygenation-treated cardiomyocytes [113].…”
Section: A Methylation In Hypertension and Cardiovascular Diseasesmentioning
confidence: 99%
“…Up to now, no consistent conclusion was reached about the link between m 6 A and hypoxia. Previous reports found that the m 6 A abundance in mRNA was increased under hypoxia stress in HEK293T cells and cardiomyocytes (37, 38). The increased m 6 A level stabilized the mRNAs of Glucose Transporter 1 (Glut1), Myc proto-oncogene bHLH transcription factor (Myc), Dual Specificity Protein Phosphatase 1 (Dusp1), Hairy and Enhancer of Split 1 (Hes1), and Jun Proto-Oncogene AP-1 Transcription Factor Subunit (Jun) without influencing their protein level (37).…”
Section: Discussionmentioning
confidence: 79%
“…Hypoxia increased demethylation by stimulating hypoxia-inducible factor (HIF)-1α- and HIF-2α–dependent over-expression of ALKBH5 (26). In addition, transcription factor EB activates the transcription of ALKBH5 and downregulates the stability of METTL3 mRNA in hypoxia/reoxygenation (H/R)-induced autophagy in ischemic diseases (38). Our study found that m 6 A abundance in total circRNAs was decreased by hypoxia exposure.…”
Section: Discussionmentioning
confidence: 99%